Faktor yang Mempengaruhi Perkembangan Industri Kreatif Subsektor Seni Kriya di Banjarmasin - Ismayanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research is conducted to know the factors that influence the developmentof creative industries craft sub-sector in Banjarmasin and How the condition of SDA,HR, technology, Marketing, and Capital, And how its influence and what the rightdevelopment strategy what is the correct development The data used is Primary data obtained through a questionnaire, interviews,and observations on the creative industries sub-sector craft art in Banjarmasin by usingdescriptive analysis and SWOT analysis. The results showed that the condition of natural resources and human resourcesis sufficient, but the quality is still low, then the technology used is relatively traditional.Simultaneously, the marketing conditions are not broad, then the capital employed isstill small because it is only limited to own wealth and family. Factors affecting thedevelopment of creative industries craft sub-sector in Banjarmasin are SDA, SDM,technology, Marketing, and capital are interrelated and each other. A strategy that canbe used based on SWOT is a horizontal strategy, which means that the creative industryshould be more expansive in its business.